Postmortem inflation and fixation of human lungs: A technique for pathological and radiological correlations. Issue 2 (March 1974) - Wright, B. M.; Slavin, G.; Kreel, L.; Callan, K.; Sandin, Brenda
Abstract : Wright, B. M., Slavin, G., Kreel, L., Callan, K., and Sandin, Brenda (1974). Thorax, 29, 189-194. Postmortem inflation and fixation of human lungs. A method of fixing lungs by inflating them with heated formalin vapour is described. This method facilitates postmortem correlations between radiographic and histological appearances.